Managerial Effiency in German Top League Soccer - Markus Kern; Bernd Süssmuth (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
This study applies stochastic frontier analytic techniques in the estimation of sporting production functions. As ex ante input factors, we use pre-seasonal estimates of wage bills of players and coaches that are transformed during the production process of a season into ex post pecuniary revenues and sporting success. While in the case of athletic output we find a robust pattern of technical efficiency over subsequent seasons, the estimates based on economic output highlight the instability of the German soccer industry.
urn:nbn:de:bvb:19-epub-5-8
Keywords: L83; C21; D24; 330; soccer economics; sporting production function; stochastic frontier